Application of Rosenthal effect in clinical teaching and training of newly recruited surgical nurses (罗森塔尔效应在手术室新入职护士带教与培训中的应用) - SHEN Jianhui (沈剑辉); ZHU Yan (朱艳) (Association of Integrative Nursing, 2022)
Objective To evaluate the Rosenthal effect in clinical teaching and training of newly recruited surgical nurses. Methods Totally 60 newly recruited surgical nurses were divided into two groups: the control group (n = 30) and the observation group (n = 30). The members of the control group received routine clinical teaching and training. A Study of Rosenthal Effect was carried out on the group members, teachers, head nurses and full-time teachers of the observation group, aiming to increase the teachers' sense of investment and initiative, drive the newly recruited nurses' learning motivation and improving their self-confidence. In the third and sixth month, all the newly recruited nurses were tested in theoretical knowledge and practical skills, and psychology and feedback from teachers was measures. Results There were significant differences in the time effect and inter group effect of the scores of theoretical test, practice assessment, professional identity and retention intention and satisfaction with teaching between the two groups(P＜0. 05). Conclusion Rosenthal Effect is conducive to improve the professional identity and investment of newly recruited surgical nurses, and reduce their turnover intention. It is of great significance to stabilize the operating room nursing staff and promote the construction of new nurses' specialization. (目的 探讨罗森塔尔效应在手术室新入职护士带教与培训中的应用。方法 60名手术室新入职护士分为对照组和观察组, 各30名。对照组按常规带教, 观察组在对照组基础上实施罗森塔尔效应实验。评估和对比两组新入职护士带教3、6个月时的理论成绩、专科操作成绩、留职意向、职业认同以及对带教老师的评价。结果 观察组带教3、6个月时的理论成绩、专科操作成绩、留职意向、职业认同以及对临床带教老师的评价分值均高于同期对照组, 差异有统计学意义(P＜0. 05)。结论 罗森塔尔效应的应用有利于提高手术室新入职护士的专科化认同及投入程度, 对于稳定手术室护理人员和推动新护士专科化建设具有重要意义。)